Experiences of sheltering during the Black Saturday bushfires: Implications for policy and research. (August 2017) - Whittaker, Joshua; Blanchi, Raphaele; Haynes, Katharine; Leonard, Justin; Opie, Kimberley
Abstract: More than half of those who died in the 2009 Black Saturday bushfires in Victoria, Australia, were sheltering inside a house at the time of their death. This marks a shift in bushfire fatality trends, which previously saw most fatalities occurring outside while residents attempted to protect assets or evacuate. This paper presents findings from research that examined people's experiences of sheltering in and exiting houses, sheds, personal shelters and other structures on Black Saturday. Qualitative data were sourced from 315 semi-structured interviews with residents affected by the bushfires and 50 witness statements presented to the Victorian Bushfires Royal Commission. Results indicate that despite limited planning and preparation specifically for sheltering on Black Saturday, many residents protected themselves from fire by sheltering inside houses, other structures and in open spaces. Most sheltered actively, engaging in regular monitoring and action to protect the shelter and occupants. However, some found sheltering challenging due to heat, smoke and responsibilities for children, vulnerable household members and the incapacitated. Misconceptions persist about the safety offered by houses and, in particular, bathrooms during bushfires. Education and advice should emphasise the need to plan and prepare for active sheltering, regardless of whether people intend to stay and defend or leave. The paper offers recommendations to promote planning and preparedness for active sheltering and identifies areas for further research.